Parallel operation of unity power factor rectifier for PMSG wind turbine system - Md Shafquat Ullah Khan (2021)
Offshore wind power has inspired the fields of high voltage direct current (HVdc) for advantages of high power transmission in long distance. Hefty wind generators are making advanced multilevel rectifier and parallel operation of rectifiers popular choice of research with the aim to accommodate higher power. Issues of reliability and complexity of control are associated with active power electronic devices at such high power. This paper focuses on the novelty of operation of parallel three-phase diode rectifiers each with auxiliary bidirectional switching blocks (BSB) to improve their performance. For the system, maximum percentage power is commuted through the three-phase diode rectifier and paralleling further lessens the current stress on the semiconductor switches present in the BSBs. Competence of continuous operation at times of any specific branch failure provides the proposed system with higher modularity and reliability. The paralleled topology is controlled to obtain unity power factor at the generator output with low generator output-current harmonics using hysteresis current control. The dc-link voltage is controlled at a reference value, for various dynamic variations along with balanced capacitor voltages. The permanence of the proposed system is simulated for scenarios associated with variation of wind speed and load demands while various operation modes are tested on a 2.5-kW experimental setup.